Development and Psychometric Properties of a Flourishing Scale for University Students: A Rasch Model Analysis - Tiara Anggun Mauladi; Anne Hafina; Eka Sakti Yudha; Reza Hadiwijaya Dynasti; Tiara Anggun Mauladi; Anne Hafina; Eka Sakti Yudha (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Flourishing is an important indicator of students' psychological well-being, especially in facing academic demands and developmental transitions in early adulthood. However, the measurement of flourishing in Indonesian students still requires a valid, reliable, and more precisely calibrated instrument. This study aims to develop and evaluate the psychometric properties of the Flourishing Scale based on the PERMA model for students using Rasch analysis. This study uses a quantitative approach with instrument development design. Participants consisted of 236 active students of the Indonesian Education University aged 18–22 years. The instrument consists of 50 items arranged based on the five dimensions of PERMA, namely Positive Emotion, Engagement, Relationship, Meaning, and Accomplishment. The data was analyzed using the Rasch Rating Scale Model through the Winsteps program. The results of the analysis showed that the instrument met the assumption of unidimensionality with raw variance explained by measures of 45.3% and unexplained variance in first contrast of 4.3%. The reliability of the person is 0.89 with a separation of 2.91, while the reliability of the item is 0.99 with a separation of 10.78. Item fit analysis showed three items, namely P7, P16, and P34, did not meet the model's suitability criteria and needed to be revised or considered for issue. The Wright map shows that the distribution of items is generally according to the level of flourishing of the respondents, although the instrument is more optimal for measuring students with medium to high flourishing levels. The PERMA-based Flourishing Scale shows good psychometric quality and can be used as an initial assessment tool to map student flourishing, noting that some items still need further refinement.